PENDIDIKAN LINGKUNGAN PADA SEKOLAH MENENGAH ATAS NEGERI DI KOTA BAUBAU - Ihsyaluddin; Jaelani, Jaelani; Firham, Firham (Geography Education Study Program, Faculty of Teacher Training and Education, 2024)
The aim of this research is to obtain information related to the implementation of environmental education at SMAN Baubau City. This research uses a qualitative descriptive approach, in collecting data using direct observation, interviews and documentation techniques. Based on the research results, it is clear that the implementation of environmental education at SMAN Kota Baubau has been implemented but there is still a need for improvement and awareness of all components, both from policy makers, leadership elements, teachers and students in cultivating environmental values, not only in the learning process but also in other activities that reflect and increase environmental awareness.